KONTRIBUSI HASIL BELAJAR PELATIHAN “MENJAHIT” TERHADAP KESIAPAN KERJA DI KONFEKSI - Liza Putri Renata; Mally Maeliah (Fesyen Perspektif, 2015)
Tailoring a training program sewing skills given to the former drug abusers aged 14 s.d 26 years as a provision back in the community and competence within the scope of expertise sewing (dressmaking). This study aimed to obtain data on the contribution of learning outcomes Tailoring Training to work in the garment readiness. The method used is descriptive analytic data collection tool using tests and questionnaires. The population in this study are alumni of the Social Rehabilitation Center Pamardi Putera (BRSPP) force in 2013 with the total sample, totaling 26 people. The results showed that the learning outcomes Tailoring Training in general are at sufficient criteria, based on the knowledge that in terms of materials knowledge, knowledge of sewing machines, techniques to correct the interference on the machine, sewing skills and safety. Conclusions from the study showed that the contribution of learning outcomes Tailoring Training to work in the garment readiness on citizens to learn generally in sufficient criteria.